PEMBERDAYAAN MASYARAKAT BERBASIS PROGRAM CSR PT. COCA-COLA AMATIL INDONESIA - Isna Siti Nuraeni; Rohmanur Aziz (Jurusan Pengembangan Masyarakat Islam, Fakultas Dakwah dan Komunikasi, UIN Sunan Gunung Dj, 2021)
This paper aims to determine the benefist obtained by the company, the level of PT Coca-Cola Amatil Indonesia concern of the people of Cihanjuang Village, and the benefits of CSR program to the environment around the company. The method used in this research is descriptive method with a qualitative approach. The results of this study indicative that the benefist of the company are short—term benefist to get to know people, the medium term is increasingly married to the community, and the long tern can establish a long lasting relationship. Than the concern of the company is that campanies rarely wait for the ball but pick up the ball. And this benefist for companies to increase product sales and get a positive image from the community. And the benefits for the community can feel the results of CSR programs and can improve the welfare of the community.